Dysregulated mesenchymal PDGFR-β drives kidney fibrosis - Buhl, Eva Miriam; Djudjaj, Sonja; Klinkhammer, Barbara M.; Ermert, Katja; Puelles, Victor G.; Lindenmeyer, Maja T.; Cohen, Clemens David; He, Chaoyong; Borkham-Kamphorst, Erawan; Weiskirchen, Ralf; Denecke, Bernd; Trairatphisan, Panuwat; et al. (EMBO molecular medicine, 2020)
Kidney fibrosis is characterized by expansion and activation of platelet-derived growth factor receptor-β (PDGFR-β)-positive mesenchymal cells. To study the consequences of PDGFR-β activation, we developed a model of primary renal fibrosis using transgenic mice with PDGFR-β activation specifically in renal mesenchymal cells, driving their pathological proliferation and phenotypic switch toward myofibroblasts. This resulted in progressive mesangioproliferative glomerulonephritis, mesangial sclerosis, and interstitial fibrosis with progressive anemia due to loss of erythropoietin production by fibroblasts. Fibrosis induced secondary tubular epithelial injury at later stages, coinciding with microinflammation, and aggravated the progression of hypertensive and obstructive nephropathy. Inhibition of PDGFR activation reversed fibrosis more effectively in the tubulointerstitium compared to glomeruli. Gene expression signatures in mice with PDGFR-β activation resembled those found in patients. In conclusion, PDGFR-β activation alone is sufficient to induce progressive renal fibrosis and failure, mimicking key aspects of chronic kidney disease in humans. Our data provide direct proof that fibrosis per se can drive chronic organ damage and establish a model of primary fibrosis allowing specific studies targeting fibrosis progression and regression.
Gesehen am 27.10.2020